Invariantes de germes singulares e poliedros de Newton - Melo, Olavo Queiroga de (Universidade Federal de São Carlos, 2025)
In this project, we study the relation between the Milnor number of an analytic function at an isolated singular point and its Newton polyhedron.
Invariants of singular germs and Newton polyhedra
Keywords: Multiplicidade; Número de Milnor; Poliedros de Newton; Multiplicity; Milnor number; Newton polyhedra; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA